Analisis Kesulitan Siswa SMA Dalam Memahami Konsep Hukum Newton - Ni Made Juliartini; Amiruddin Hatibe; Darsikin Darsikin (Faculty of Teacher Training and Education, Musamus University, 2020)
This research is a qualitative descriptive study that aims to analyze the difficulties of students of SMA Negeri 3 Palu. The subjects of this study were 26 students of SMA Negeri 3 Palu grade 11th IPA in the 2018/2019 academic year, 26 students who were divided into three categories: high, medium and low level based on the results of Respondent Selection Test (TSR). 2 respondens in each category were given a thinking-aloud test (TA). The instrument used in this study was a TSR consisting of 25 reasoned multiple choice questions and an essay test conducted in TA consisting of 6 essay questions. The results shoewd that difficulty of concepts understanding experienced by students divided into 4 types, namely: (1) difficulty of facts understanding, (2) difficulty of concepts understanding, (3) difficulties of operating and calculation processes, and (4) difficulty of principle understanding. Based on the results of the overall percentage of types shows that in general the difficulty of students' understanding concepts is in the high category with a percentage of difficulty of 67.5% and the factors that cause difficulties in understanding students' physics concepts consist of two factors namely external factors and internal factors.